Assessing the Structural Correlates between Friendship Networks and Conversational Agency in Facebook Groups - Polonski, Vyacheslav; Hogan, Bernie (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
To what extent do friendship ties influence the conversation structure in open groups? Openly accessible Facebook groups offer the opportunity to examine how individuals leverage their existing friendship relations when speaking to a large and often heterogeneous audience. For example, those with many friends in the group may receive more positive signals from others and also may have their content validated more easily. Thus, while the group is ostensibly open to all, existing relationships may impede such openness on a practical level. We employ a stratified sample of 30 Facebook groups from UK Russell Group universities. Using multilevel regression, we examine the effects of several structural metrics at both the actor and group level on the magnitude of three conversational metrics: likelihood of initiating a conversation, responding to a conversation and receiving responses for content. We find that aspects of individual network positions, e.g. degree-centrality and eigenvector-centrality, as well as qualities of the group e.g. group-density and modularity, have a consistent and highly significant effect on conversational metrics, while the strength of these relationships clearly varies by group type. We contextualise our findings via Gibson’s notion of “conversational agency”, and point to future directions for designing and managing online communities.